Use of the GORE® CARDIOFORM Septal Occluder for percutaneous closure of secundum atrial septal defects: Results of the multicenter U.S. IDE trial. Issue 7 (28th February 2020) - Gillespie, Matthew J.; Javois, Alexander J.; Moore, Phillip; Forbes, Thomas; Paolillo, Joseph A.; ,
Abstract: Objective: To evaluate safety and efficacy of the GORE® CARDIOFORM Septal Occluder for percutaneous transcatheter closure of ostium secundum atrial septal defects. Background: The GORE® CARDIOFORM septal occluder is a double‐disc, low profile, soft, conformable device, with distinct advantages over the GORE® HELEX® Septal Occluder. Methods: Subjects were enrolled in this single arm prospective study from 21 U.S. sites, and followed for 3 years. Primary endpoint was 6 month composite clinical success, comprised of technical success (implantation and retention of device), closure success (normalization of right heart size), no 30 day serious adverse events, and no device embolization or reintervention. Secondary endpoints included technical success, procedure success (technical success and ≤ 2 mm residual shunt at procedure conclusion), closure success (clinically insignificant or no residual shunt), and safety (freedom from 30 day serious adverse events and 6‐month device events). Results: Between October 2012 and May 2015, 50 pivotal and 350 continued access subjects underwent attempted transcatheter GORE® CARDIOFORM Septal Occluder implantation. Median age was 6.9 years, and mean static defect diameter 9.7 ± 3.1 mm. Device placement was achieved in 93.5% (374/400). Composite clinical success was 90.2% and clinical closure success was 98.8% at 6 months. Freedom from serious adverse events was 98.3% at 30 days, with no device embolizations or reinterventions through 6 months. Conclusions: The GORE® CARDIOFORM Septal Occluder has high composite clinical success and safety, performing well in defects ≤17 mm by stop flow stretched diameter. Single, multifenestrated, and deficient retroaortic tissue defects were well represented and successfully treated.